ANALISIS VALUE FOR MONEY DALAM MENILAI KINERJA KEUANGAN DESA (Studi di Desa Telaga Kecamatan Lenangguar Tahun Anggaran 2016-2020) - Ika Fitriani; Muhammad Nur Fietroh; S Sahida (Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study was to know the performance of village apparatus in village financial management of Telaga village, Lenangguar sub-district in 2016-2020 using effectiveness and efficiency measurements.The type of this study was quantitative descriptive.The data used in this study were qualitative and quantitative data.The data used was secondary data.The secondary data in this study was the accountability report data on the realization of Village Government Budget in 2016-2020 obtained from Telaga village government, Lenangguar Sub-District.Data collection techniques used were documentation and literature study.The data analysis technique used was value for money approach. Results of the study showed that the financial performance of Telaga village if seen from the effectiveness in 2016, 2017, 2018, 2019 and 2020, village finance was very effective because the value obtained was more than 100%.Furthermore, the financial performance of Telaga village if seen from the efficiency was very efficient for the Village Fund Allocation (ADD) for Telaga village finances.For the year of 2016-2020, the village financial of Telaga village had been efficient because the value obtained was more than 100%.The performance of the village financial if seen from the economic level of the Telaga village was very economical.For the year of 2016-2020 Telaga village financial had been already economical because the value obtained was more than 100%.